2016
DOI: 10.3892/mmr.2016.5667
|View full text |Cite
|
Sign up to set email alerts
|

Impact of siRNA targeting of β-catenin on differentiation of rat neural stem cells and gene expression of Ngn1 and BMP4 following in vitro hypoxic-ischemic brain damage

Abstract: The aim of the present study was to investigate the possible damage-repair mechanisms of neural stem cells (NSCs) following hypoxic-ischemic brain damage (HIBD). NSCs obtained from Sprague Dawley rats were treated with tissue homogenate from normal or HIBD tissue, and β-catenin expression was silenced using siRNA. The differentiation of NSCs was observed by immunofluorescence, and semiquantitative reverse transcription-polymerase chain reaction and western blot analysis were applied to detect the mRNA and prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…It has been tested in Human embryonic stem cells, a glial cell line and a hES cell line to detect Nestin immunoreactivity (Vallier et al, ). Validation in adult rats as in both neuroepithelial progenitor cells of the V‐SVZ (Fu et al, ) and in NSCs obtained from brain homogenates (Zhang et al, ). In adult dogs expression of Nestin in circumventricular organs has been reported by use of this antibody (Oliveira, Fernández, Solé, & Pumarola, ). Rabbit polyclonal anti‐doublecortin (Abcam Cat# ab18723 RRID:AB_732011), an affinity‐purified antibody that recognizes an epitope located at the C‐terminus of doublecortin protein (DCX).…”
Section: Methodsmentioning
confidence: 99%
“…It has been tested in Human embryonic stem cells, a glial cell line and a hES cell line to detect Nestin immunoreactivity (Vallier et al, ). Validation in adult rats as in both neuroepithelial progenitor cells of the V‐SVZ (Fu et al, ) and in NSCs obtained from brain homogenates (Zhang et al, ). In adult dogs expression of Nestin in circumventricular organs has been reported by use of this antibody (Oliveira, Fernández, Solé, & Pumarola, ). Rabbit polyclonal anti‐doublecortin (Abcam Cat# ab18723 RRID:AB_732011), an affinity‐purified antibody that recognizes an epitope located at the C‐terminus of doublecortin protein (DCX).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, it has been shown that hypoxia and FCI increase the number of NS/PCs in the hippocampus and SVZ, promote the expansion of neuroblasts 1 month after MCAO, and that canonical Wnt signaling is involved in this process ( Cui et al, 2011 ; Zhang et al, 2014 ; Knotek et al, 2020 ). The importance of Wnt signaling in the differentiation of NS/PCs to neurons under ischemic conditions was also documented by Zhang et al (2016) . Congruent with these findings, Zhang and Chopp (2016) highlighted the stroke-induced activation of NS/PCs, and their subsequent differentiation to neuroblasts, in their review.…”
Section: Introductionmentioning
confidence: 93%
“…Thus, since ALK2 acts as a downstream mediator of the STI1 neuroprotection pathway, it may be useful as a therapeutic target for ischemic brain injury (Beraldo et al, 2018 ). It was also shown that activin A reduces brain edema and the release of inflammatory cytokines in neonatal rats after hypoxic-ischemic brain damage and plays a role in nerve regeneration and functional repair, by increasing nestin protein expression, as well as the number and differentiation of neural stem cells (Peng et al, 2006 ; Zhang et al, 2016 ).…”
Section: Treatment Of Brain Injury Targeted To Activin Amentioning
confidence: 99%